An Innovative Solar Pump Applicable in Water Distribution Networks - Hana Javadi Nejad; Behrouz Pirouz; Michele Turco; Seyed Navid Naghib; Stefania Anna Palermo; Patrizia Piro (Engineering Proceedings)
The analysis of GHG emissions for different sectors shows that one of the main contributions, responsible for 25%, is electricity and heat production. An important aspect of electricity use concerns motor pumps, which are used for both urban water supply and agricultural water systems. Generally, the highest consumption corresponds to summer, when the maximum solar radiation makes the use of solar water pumps possible. However, the total conversion of energy by conventional solar pumps is about 10% of the solar energy. This low efficiency has limited the choice of solar water pumps to areas without alternative power sources. Moreover, the final efficiency will further decrease due to that of other parts of the system, so, in order to achieve higher efficiency and sustainability, a novel method for solar water pumps must be developed. The new solar pump that we propose will take advantage of the efficiency of solar concentration dishes to absorb solar radiation, which is about 80–90%, will pump water using water vapor pressure, and will not need an electrical motor. It will offer several benefits besides high efficiency in pumping water, like the number of mechanical parts required and their maintenance costs, making its application easy and removing the limitations of typical systems.